Resource allocation algorithm for the downlink of multi-carrier and multi-user NOMA systems - Jie YAN; Rongfang SONG (Dianxin kexue)
Non-orthogonal multiple access (NOMA) technology had received considerable attention as a candidate technology for 5G cellular systems.The resource allocation problem in multi-carrier and multi-user downlink NOMA systems were studied with the goal of optimizing system throughput.In the solution of the problem,the linear water-filling power allocation was used between subcarriers as the fractional transmit power allocation algorithm was used between the superposed users,so that system throughput could be improved.Meanwhile,the concept of time slot was adopted in the design of NOMA transmission scheme,in order to be able to schedule more users in the scenario where the number of cellcenter users and celledge users were not equal.The whole time period was divided into two time slots.On the basis of ensuring the fairness of users,different user pairing groups were implemented in different time slots so as to fully utilizing the entire resource to improve system throughput.The simulation results show that this method can transmit more bits under the same transmit power comparing with traditional non-orthogonal multiple access(NOMA) and OFDMA.